Improvement in the Retention Rate of Transplanted Fat in Muscle by Denervation. (10th July 2018) - Shi, Nian; Guo, Shuzhong; Su, Yingjun; Zhang, Zhaoxiang; Qiu, Lihong; Yu, Zhou; Yang, Qing; Wang, Na; Yi, Chenggang
Abstract: Background: Improvement in the retention rate of transplanted fat is currently a topic of interest. The retention of transplanted fat relies heavily on the reestablishment of blood supply and the function of the adipose-derived stem cells (ADSCs), which may both be impeded by mechanical force. However, the effect of mechanical force on the retention of adipose implants remains unclear. Objectives: This study aimed to evaluate the effectiveness of immobilization on fat retention rate. Methods: Immobilization was carried out by denervation of the hind limb of rats to reduce the mechanical force. Sprague-Dawley (SD) rats were used, and the two hind limbs were assigned at random to the immobilization side and the control side. On average, 0.4 mL of fat was injected into the bilateral muscle and subcutaneous space of the hind limb, and 6 rats were sacrificed at each time point. The outcome measures included the retention rate, the histologic evaluation, and the density of new vessels and proliferative ADSCs. Results: For the muscle fat, the retention rate improved, and more proliferative ADSCs and new vessels were found in the immobilization group. The histologic evaluation between the two sides was of no statistical significance. For the fat in the subcutaneous space, no statistical difference was observed in all the outcome measures between the two sides. Conclusions: Regional immobilization of the recipient site by denervation can improve the retention of the fat graft in muscles owing to improved density of the new vessels and proliferative ADSCs.